Photosynthetic seasonality of global tropical forests constrained by hydroclimate - Guan, K.; Pan, M.; Li, H.; Wolf, A.; Wu, J.; Medvigy, D.; Caylor, K.K.; Caylor, K.K.; Wood, E.F.; Malhi, Y.; Liang, M.; Kimball, J.S.; et al.
The response of tropical forests to droughts is highly uncertain. During the dry season, canopy photosynthesis of some tropical forests can decline, whereas in others it can be maintained at the same or a higher level than during the wet season. However, it remains uncertain to what extent water availability is responsible for productivity declines of tropical forests during the dry season. Here we use global satellite observations of two independent measures of vegetation photosynthetic properties (enhanced vegetation index from 2002 to 2012 and solar-induced chlorophyll fluorescence from 2007 to 2012)to investigate links between hydroclimate and tropical forest productivity. We find that above an annual rainfall threshold of approximately 2,000 mm yr -1, the evergreen state is sustained during the dry season in tropical rainforests worldwide, whereas below that threshold, this is not the case. Through a water-budget analysis of precipitation, potential evapotranspiration and satellite measurements of water storage change, we demonstrate that this threshold determines whether the supply of seasonally redistributed subsurface water storage from the wet season can satisfy plant water demands in the subsequent dry season. We conclude that water availability exerts a first-order control on vegetation seasonality in tropical forests globally. Our framework can also help identify where tropical forests may be vulnerable or resilient to future hydroclimatic changes.
Keywords: CLIMATOLOGY; PHOTOSYNTHESIS; POTENTIAL EVAPOTRANSPIRATION; RAINFOREST; SATELLITE IMAGERY; SEASONALITY; THRESHOLD; TROPICAL FOREST; VEGETATION STRUCTURE; VULNERABILITY; WATER AVAILABILITY